The Effects Of Formalin And Sodium Chloride On Ectoparasites Of Imported Grass Carp (Ctenopharyngodon Idella Cuvier And Valenciennes 1844) Fingerlings. - Soemarno, Rindayuni T. (1993)
Four shipments of grass carp imported from Indonesia were used for this study . The grass carp ( Ctenopharyngodon idella Cuvier and Valenciennes 1844) finger lings were infected by the monogenean ( Dactylogyrus lamellatus Akhrnerov 1952) ; protozoans ( Trichodina spp . , Trichodinella sp . ,Trichophrya sp . ,Cryptobia branchialis Nie , Ichthyophthirius multifiLiis Fouquet 1876 and Piscinoodinium pillulare Schaperclaus 1954); trematodes ( metacercariae of Echinostomatidae and Transversotrema sp . ) and a crustacean ( Argulus sp . ) . Dactylogyrus lamellatus Akhrnerov 1952 obt a ined in this study were comparat ively smaller than those previously described from USSR and Hungary .Transversotrema sp . wa s found underneath the scales of grass carp . It differed in shape , size and certain morphological details to other previously described species .Histopathological study carried out on the gills infected by echinostomatid metacercariae showed severe swollen chondrocytes, epithelial hyperplasia, squamous metaplasia of epithelial cells,atrophy,haemorrhages,necrosis and obliteration of blood vessels .